Tethered swimming and dry land force parameters: useful tools to characterize front crawl performance in both genders - Morouço, Pedro Gil Frade (2014)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2014-09-26T20:59:47Z No. of bitstreams: 1 PhD Pedro Morouço.pdf: 1801296 bytes, checksum: 9add95a175c9576c369a4fd39b9a017a (MD5)